Pendidikan manusia Indonesia - Widiastono, Tonny D. (Jakarta : Penerbit Buku Kompas, 2004)
The educational system in Indonesia; festschrift in commemorating the 30th anniversary of Yayasan Toyota & Astra
Includes bibliographical references and index
Keywords: Education -- Indonesia; Indonesia -- History and criticism -- Education